Quaternionic Fourier transform for enhancement and compression of color images - Tigran Manukyan (Изд-во НАН РА)
This paper presents color image processing and analysis using quaternionic Fourier transform (QFT). Algorithm of color image enhancement is described. Image compression using QFT is considered. Results using the suggested method are compared with the results using existing methods.
Keywords: Mathematics; Algorithm